Diabetes Awareness Among Patient's Attendant Visiting in Teaching Hospital of Eastern Nepal - Ghimire, Hridaya Bibhu; Parajuli, P; KC, Heera; Parajuli, SB (Birat Journal of Health Sciences, 2017)
IntroductionDiabetes is a prevalent non-communicable disease. It has  increasing global trend. In Nepal, the prevalence of diabetes is also increasing. Awareness is vital to  revent and early diagnosis of diabetes.ObjectivesThe objective of study was to assess the awareness of diabetes and its related factors.MethodologyThis was a hospital based cross sectional study. Total of 503 patient's a